1994
DOI: 10.1111/j.1432-2277.1994.tb01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose heparin: a novel approach in immunosuppression

Abstract: Very low subcutaneous doses of standard and low molecular weight heparin inhibited the traffic of sensitized lymphocytes to a graft site, reduced in situ mononuclear cell infiltration and prolonged skin allograft survival in mice. Similar effects were caused by low doses of oral heparin, while higher oral doses prolonged graft survival. Our results suggest that oral heparin may have immunosuppressive properties applicable in clinical transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Very low subcutaneous doses of standard and low‐molecular‐weight heparin inhibited the traffic of sensitized lymphocytes to a graft site, reduced in situ mononuclear cell infiltration and prolonged skin allograft survival in mice. Similar effects were caused by low doses of oral heparin (16).…”
Section: Discussionmentioning
confidence: 74%
“…Very low subcutaneous doses of standard and low‐molecular‐weight heparin inhibited the traffic of sensitized lymphocytes to a graft site, reduced in situ mononuclear cell infiltration and prolonged skin allograft survival in mice. Similar effects were caused by low doses of oral heparin (16).…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, heparin has immunoregulatory functions as well as it binds to cytokines and growth factors such as tumor necrosis factor (TNF) and extracellular matrix proteins (ECM), thus regulating the leukocytes. [15][16][17] It is believed that LMWH reduces the risk of cancer-associated thrombosis (CAT). 34 However, it is associated with quite severe adverse events, as it is the heparin-induced thrombocytopenia (HIT).…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent studies have shown that LMWH has immunoregulatory functions and leads to immunosuppression. [15][16][17] Regarding this term, an important question arises, namely, whether the LMWH during the postoperative hospitalization of gastrointestinal cancer patients is linked to infection, which the presents study aims to answer.…”
Section: Introductionmentioning
confidence: 99%